Distribution of transplanted human mesenchymal stem cells from Wharton’s Jelly in the central nervous systems of the EAE rats - Kovalchuk, M.V.; Deryabina, O.G.; Pichkur, L.D.; Verbovskaya, S.A.; Shuvalova, N.S.; Pichkur, O.L.; Kordium, V.A. (Вiopolymers and Cell, 2015)
Human Wharton’s Jelly MSCs (hWJ-MSCs) have a considerable advantage and potential in treating the central nervous system diseases and can be a new alternative treatment of Multiple Sclerosis (MS). Aim. To study the persistence and distribution of hWJ-MSCs along the neuraxis following transplantation in central nervous system of rats with experimental autoimmune encephalomyelitis (EAE), the animal model of MS. Methods. Isolation and cultivation of hWJ-MSCs in vitro. Immunological phenotyping by flow cytometry. EAE induction. Intrathecal (suboccipital) injection of MSCs into CNS of SCH-induced EAE rats. Persistence of hWJ-MSCs in the CNS of hWJ-MSCs -treated rats was detected through detection of the human alpha-satellite DNA in the tissue sections and the cerebrospinal fluid (CSF) by PCR at days 2, 3, 4 and 5 Results. PCR-assays for alpha-satellite sequences revealed that Human DNA was detected during 5 days following intrathecal injection at the peak of disease in the treated rats. It has been demonstrated that the human DNA was traced in CSF and various segments of a spinal cord. Conclusions. The data obtained suggest that intrathecally delivered hWJ-MSCs, with time, can migrate through the CSF from the injection site to various segments of CNS and persist therein during the first week of post transplantation, which was performed at the EAE disease peak in the xenogeneic setting without immunosuppression. hWJ-MSCs may be considered as a delivery cell source of therapeutic molecules for CNS inflammatory diseases. Мезенхімальні стовбурові клітини Вартонового студня пуповини людини (МСК-ВС) мають значну перевагу і потенціал у лікуванні захворювань центральної нервової системи (ЦНС) і можуть стати новою альтернативною терапією для розсіяного склерозу (РС). Мета. Вивчити виживання і розподіл МСК-ВС в ЦНС щурів з ЕAЕ після субокціпітальної трансплантації. Методи. Виділення і культивування МСК-ВС in vitro. Імунологічне фенотипування методом проточної цитофлюориметрії. Індукція ЕАЕ. Інтратекальне введення МСК в ЦНС щурів лінії Wistar з ЕАЕ, індукованим гомогенатом спинного мозку (ГСМ). Виживання МСК-ВС в ЦНС щурів оцінювали за допомогою виявлення людської альфа-сателітної ДНК у зразках тканин та спинномозковій рідині (СМР) на 2, 3, 4, та 5 дні за допомогою ПЛР. Результати. ПЛР-аналіз для альфа-сателітних послідовностей показав, що ДНК людини виявлялася протягом 5 днів після інтратекального введення, на піку симптомів. Було показано, що трансплантовані ксеногенні МСК-ВС мігрували через СМР в різні сегменти спинного мозку. Висновки. Отримані результати дозволяють припустити, що МСК-ВС, введені інтратекально, можуть мігрувати зі струмом СМР в різні відділи ЦНС і перебувати в них протягом першого тижня після трансплантації на піку захворювання ЕAЕ в ксеногенному варіанті без імуносупресії. МСК-ВС можна розглядати як джерело клітин для доставки терапевтичних молекул для лікування запальних захворювань ЦНС. Мезенхимальные стволовые клетки Вартонового студня пуповины человека (МСК-ВС) имеют значительное преимущество перед другими видами стволовых клеток и потенциал в лечении заболеваний центральной нервной системы (ЦНС) и могут стать новой альтернативной терапией для рассеянного склероза. Цель. Изучить выживание и распределение МСК-ВС в ЦНС крыс с ЭАЭ после субоксипитальной трансплантации. Методы. Выделение и культивирование МСК-ВС in vitro. Иммунологическое фенотипирование методом проточной цитофлюориметрии. Индукция ЭАЭ. Интратекальное (субокципитальное) введение МСК в ЦНС крыс линии Wistar с ЭАЭ, индуцированным гомогенатом спинного мозга (ГСМ). Выживание МСК-ВС в ЦНС крыс оценивали с помощью выявления человеческой альфа-сателлитной ДНК в образцах тканей и спинномозговой жидкости (СМЖ) на 2, 3, 4 и 5 дни с помощью ПЦР. Результаты. ПЦР-анализ для альфа-сателлитных последовательностей показал, что ДНК человека обнаруживалась в течение 5 дней после интратекального введения, на пике симптомов. Было показано, что трансплантированные ксеногенные МСК-ВС мигрировали через спинномозговую жидкость (СМЖ) в различные сегменты спинного мозга. Выводы. Полученные результаты позволяют предположить, что МСК-ВС, введенные интратекально, со временем¸могут мигрировать с током СМЖ в различные отделы ЦНС и находиться в них на протяжении первой недели после трансплантации на пике заболевания ЭAЭ в ксеногенном варианте без иммуносупрессии . МСК-ВС можно рассматривать как источник клеток для доставки терапевтических молекул для лечения воспалительных заболеваний ЦНС.